Aortic Response to Strength Training and Spirulina platensis Dependent on Nitric Oxide and Antioxidants - Brito, Aline de Freitas; Silva, Alexandre S.; de Souza, Alesandra A.; Ferreira, Paula B.; de Souza, Iara L. L.; Araujo, Layanne C. da Cunha; Félix, Gustavo da Silva; Sampaio, Renata de Souza; Silva, Maria da Conceição C.; Tavares, Renata L.; Pereira, Reabias de Andrade; Miranda Neto, Manoel; et al. (Frontiers in Physiology, 2018)
Studies have shown that supplementation with Spirulina platensis improves vascular reactivity. However, it is unclear whether in association with strength training this effect can be enhanced. Thus, this study aimed to determine the effects of strength training and S. platensis on the reactivity of the aorta from Wistar rat and the possible mechanisms involved. The animals were supplemented with S. platensis and divided into sedentary (SG, SG50, SG150, and SG500) and trained groups (TG, TG50, TG150, and TG500). Nitrite, malondialdehyde (MDA) and antioxidant activity were determined by biochemical assays. To evaluate vascular response, cumulative concentration response curves to phenylephrine (PHE) and acetylcholine (ACh) were constructed. L-NAME was used to assess the participation of nitric oxide (NO). It was observed that the PHE contractile potency was reduced in TG50, TG150, and TG500 groups compared to SG50, SG150, and SG500 groups, respectively. However, the presence of L NAME increased the contractile response in all groups. Strength training potentiated the increase in relaxing activity induced by S. platensis, where the pCE50 values of ACh increased in TG150 and TG500. These responses were accompanied by increased nitrite production, MDA reduction and increased antioxidant activity in the aorta of both TG150 and TG500 groups. Thus, the present study demonstrated that combined with strength training, S. platensis potentiates vascular improvement through the participation of NO and reduction of oxidative stress.